KEPAILITAN LINTAS BATAS PERSPEKTIF HUKUM INTERNASIONAL DAN PERBANDINGANNYA DENGAN INSTRUMEN NASIONAL DI BEBERAPA NEGARA - Loura Hardjaloka (Universitas Airlangga, 2015)
Currently cross-border insolvency is not a new thing since free trade requires loan agreement with foreign parties. The issues with debtor's assets confiscation in other countries are the recognition and implementation of the domestic’s court decision in other countries and vice versa. Based on normative juridical research, Indonesia, Thailand, and Singapore do not recognize bankruptcy decision from other states domestic court due to the application of territoriality principle that debtor's assets in these countries cannot be confiscated by foreign creditors and the bankruptcy decision by those courts will not be recognized and implemented in other countries. With cross-border insolvency bilateral agreements such as between Singapore and Malaysia, the bankruptcy decision of each country can be recognized and implemented in countries which enter into agreements. Different to Japan and South Korea which apply the universality principle so that domestic bankruptcy decision may apply to the debtor's assets abroad and vice versa.